Resistance of non-lactating ewes and lambs of indigenous and crossbreds to natural infection with Haemonchus contortus - Singh, Satyaveer; Yadav, C L; Banerjee, D P (The Indian Journal of Animal Sciences, 2012)
The resistance or non-lactating Nali, 50% Nali x 50% Russian Merino/Corriedale, 37.5% Nali x 62.5% Russian Merino /Corriedale and 25% Nali Â x 75% Russian Merino/Corridale ewes naturally infected with Haemonchus contortus was compared . No significant differences were found between ewes of Nali and 50% Nali while 37.5% Nali and 25% Nali ewes tended to show higher egg counts. further, the susceptibility of weaned lambs belonging to Nali and its crosses (50% and 37.5% Nali) showed no signilicant differences except significantly higher body weights in 50% Nali lambs compared to Nali. Sentinel lambs indicated that pastures were contaminated.